2015
DOI: 10.3390/en8042575
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Ethanol Production from Brewers’ Spent Grain

Abstract: Ethanol production from lignocellulosic biomasses raises a global interest because it represents a good alternative to petroleum-derived energies and reduces the food versus fuel conflict generated by first generation ethanol. In this study, alkaline-acid pretreated brewers' spent grain (BSG) was evaluated for ethanol production after enzymatic hydrolysis with commercial enzymes. The obtained hydrolysate containing a glucose concentration of 75 g/L was adopted, after dilution up to 50 g/L, for fermentation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 26 publications
(27 reference statements)
1
48
0
2
Order By: Relevance
“…Dioxin levels in the fly-ash from the nearby incinerator were more than 20 times the EU limits [17]. Moreover, soil and incinerator emissions measurements at several sites in Iceland such as Kirkjubaejarklaustur revealed that emissions were 85 times the EU limits [6,18]. These problematic findings resulted in the widespread testing of soil across Iceland [17], shutdown of several incinerators [18], withdrawal of some Icelandic meat and milk from the markets and culling of all the livestock on the farms impacted [17].…”
Section: Resource Levelmentioning
confidence: 97%
See 1 more Smart Citation
“…Dioxin levels in the fly-ash from the nearby incinerator were more than 20 times the EU limits [17]. Moreover, soil and incinerator emissions measurements at several sites in Iceland such as Kirkjubaejarklaustur revealed that emissions were 85 times the EU limits [6,18]. These problematic findings resulted in the widespread testing of soil across Iceland [17], shutdown of several incinerators [18], withdrawal of some Icelandic meat and milk from the markets and culling of all the livestock on the farms impacted [17].…”
Section: Resource Levelmentioning
confidence: 97%
“…Lignocellulosic materials, a third group of feedstocks, represents the most viable option for bioethanol production. Increasing food demand and the need to feed an increasing global population could make conventional agricultural crops less competitive and more costly sources compared to lignocellulosic materials [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The yeast strain adopted for ethanol fermentation was S. cerevisiae LPB-287 selected in our previous work (Liguori et al, 2015a). The yeast was inoculated in three 250 mL flasks containing 100 mL of YM broth whose composition in (g/L -1 ) is as follows: glucose (10), peptone (5), malt extract (3), yeast extract (3).…”
Section: S Cerevisiae Inoculum and Medium Preparation For Fermentatimentioning
confidence: 99%
“…Based on this, the aim of this work was to analyze the strains Saccharomyces cerevisiae LPB-287 (Liguori et al, 2015a) and Lactobacillus acidophilus ATCC 43121 (Liguori et al, 2015b) for their ability to grow on the A. platensis residual biomass after high value metabolites extraction by either supercritical fluid extraction (SFE) or microwave-assisted extraction (MAE) and produce ethanol and lactic acid, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the predominant bioethanol is generally used blended with gasoline to push down the usage of conventional fuel and can be used in existing motor engines [1]. Bioethanol is a liquid resulting from fermentation of sugar and it is sourced from plants containing carbohydrates (starch) [2].…”
Section: Introductionmentioning
confidence: 99%